Sustainability Analysis and Actor Performance in the Governance of the Turtle Conservation Program at the Turtle Conservation and Education Center (TCEC) Bali: Analisis Keberlanjutan dan Kinerja Aktor dalam Tata Kelola Program Konservasi Penyu di Turtle Conservation and Education Center (TCEC) Bali - Raditya Hafizhan Syaputra; Sambas Basuni; Nimmi Zulbainarni (Journal of Global Sustainable Agriculture, 2025)
Community-based conservation is a strategic approach to biodiversity conservation, especially in areas with strong social and cultural ties to natural resources. However, the effectiveness of collaborative governance within this approach is often not fully understood, particularly in relation to the dynamics of power relations and interdependence between actors. This study aims to analyze the roles, influences, and relationships among key actors in supporting the performance of sea turtle conservation programs at the Turtle Conservation and Education Center (TCEC) in Serangan, Bali. Using a mixed-method approach, this study combines MACTOR analysis to map the influence-dependence structure of eight key actors and quantitative descriptive analysis to assess management performance based on the perceptions of 30 respondents. The results show that Bandesa Adat Serangan has the highest influence as the holder of socio-cultural legitimacy, while TCEC Management is the most central actor with the highest level of dependence on multi-actor support. TCEC management performance is generally rated as Good to Very Good, with the highest scores for Sea Turtle Population Conservation (4.60) and Education (4.55). These findings confirm that synergy between customary institutions and formal managers is a key factor in the success of conservation governance. The resulting policy implications encourage the strengthening of community-based collaborative mechanisms in the design and implementation of sustainable coastal conservation programs.